Implementation of Round Key AES with Honey Technique for Securing the Public Cloud Data Storage - L, Selvam; Renjit J, Arokia (International Journal of Engineering and Technology, 2018)
Recent security incidents on public cloud data storage had raised concerns on cloud data security. Development in the hacking area has risen in the past few years. Due to this, Cyber Security is needed which plays an important role to cover the secret information. Currently, the attack of challenging channel is both the symmetric as well as the asymmetric encryption algorithm. Since, in both criteria the secret key has to be transmitting through a security challenging channel. For this many techniques have been put forward. The Main focus is on the vulnerabilities of the private keys while hoarded in different places for the fast utilization of the round key of the AES algorithm. In the view of the hackers, extracting the private key is nearly as same as obtaining the plain text itself. So, the honey encryption technique is used to futile the attacker by producing the fake key for each and every try of the Key puncher. An indication will be generated automatically to the storage manager when an attempt is made by the attacker. The Honey encryption is the best algorithm to overcome the drawbacks of the AES algorithm but it has some time constraints which are also eliminated here. Thus, eliminating the Brute Force Attack and providing a secure system for storing the secret key.Â Â